REPRODUCTION, LARVAL REARING AND THE INFLUENCE OF DIETARY PROTEIN LEVELS ON THE GROWTH OF THE CATFISH CHRYSICHTHYS NIGRODIGITATUS (LACEPEDE) (1992)
Reproduction and early development were studied in the catfish Chrysichthys nigrodigitatus (Lacepede). From the monthly analysis of gonado-somat ic indices it was shown that the species had an annual reproductive cycle that falls into four distinct phases. The gonad preparatory phase was observed between September and December, the prespawning or maturing phase was between January and February, the spawning phase was in March and Apri1 and possib1y May, whi1e the resting phase occurred during June to August. In the males, two distinct reproductive phases were indicated. These were the gonad preparatory phase or growth phase which occurred between July and February, and the spawning phase which occurred during March to May. C. nigrodigitatus was observed to store up lipids in its muscle and liver during the initial period of gonadal growth. The lipids were later utilized for gonadal maturation, spawning activities and parental care. Observed environmental features coinciding with spawn1ng 1n sexually mature individuals in Asejire lake included low water level, presence of suitable spawning substrate, direct contact with mature partner in the absence of light and a gentle flow of water across the spawning substrate. In the presence of these features, spawning occurred within 48 hours when gravid male and female were paired in Asejire lake. The fertilized eggs from the Asejire stock hatched in the laboratory between 48 and 50 hours. The development and growth of the early larvae are described. Results of two weeks of exogenous feeding trials showed that the larvae of C. nigrodigitatus fed on live plankton had specific growth rate of 13.24 and 26% survival while those fed on 40% crude protein level had specific growth rate of 1.46 and 2% survival. Larvae fed on 35% and 30% dietary crude protein levels survived for only 5 days. Effects of different levels of crude protein diets fed to fingerlings, juvenile fish and adults of both sexes were evaluated. It was found that the fingerlings and juvenile fish had best growth in the diet containing 35% crude protein. The male and female adults had best growth on 25% and 35% crude protein respectively. Results of carcass analysis showed that the percentage of body fat increased significantly (p < 0.05) with increasing dietary protein levels while there was no significant (p>0.05) increase in the percentage of body protein. This suggests that the weight gain in the fish resulted from fat deposition. The general increase in the percentage of body fat of the adult fish compared with that of the young fish further confirm that fat deposition is an essential energy reserve in preparation for-breeding season.